Stent Design, Restenosis and Recurrent Stroke After Carotid Artery Stenting in the International Carotid Stenting Study. Issue 11 (November 2019) - Müller, Mandy D.; Gregson, John; McCabe, Dominick J.H.; Nederkoorn, Paul J.; van der Worp, H. Bart; de Borst, Gert J.; Cleveland, Trevor; Wolff, Thomas; Engelter, Stefan T.; Lyrer, Philippe A.; Brown, Martin M.; Bonati, Leo H.
Abstract : Background and Purpose—: Open-cell carotid artery stents are associated with a higher peri-procedural stroke risk than closed-cell stents. However, the effect of stent design on long-term durability of carotid artery stenting (CAS) is unknown. We compared the medium- to long-term risk of restenosis and ipsilateral stroke between patients treated with open-cell stents versus closed-cell stents in the ICSS (International Carotid Stenting Study). Methods—: Patients with symptomatic carotid stenosis were randomized to CAS or endarterectomy and followed with duplex ultrasound for a median of 4.0 years. We analyzed data from patients with completed CAS procedures, known stent design, and available ultrasound follow-up. The primary outcome, moderate or higher restenosis (≥50%) was defined as a peak systolic velocity of >1.3 m/s on ultrasound or occlusion of the treated internal carotid artery and analyzed with interval-censored models. Results—: Eight hundred fifty-five patients were allocated to CAS. Seven hundred fourteen patients with completed CAS and known stent design were included in the current analysis. Of these, 352 were treated with open-cell and 362 with closed-cell stents. Moderate or higher restenosis occurred significantly less frequently in patients treated with open-cell (n=113) than closed-cell stents (n=154; 5-year risks were 35.5% versus 46.0%; unadjusted hazard ratio, 0.68; 95% CI, 0.53–0.88). There was no significant difference in the risk of severe restenosis (≥70%) after open-cell stenting (n=27) versus closed-cell stenting (n=43; 5-year risks, 8.6% versus 12.7%; unadjusted hazard ratio, 0.63; 95% CI, 0.37–1.05). The risk of ipsilateral stroke beyond 30 days after treatment was similar with open-cell and closed-cell stents (hazard ratio, 0.78; 95% CI, 0.35–1.75). Conclusions—: Moderate or higher restenosis after CAS occurred less frequently in patients treated with open-cell stents than closed-cell stents. However, both stent designs were equally effective at preventing recurrent stroke during follow-up. Clinical Trial Registration—: URL: http://www.isrctn.com/ . Unique identifier: ISRCTN25337470.